Juridical Reviews on Branchless Banking Toward the Potential of Fraud Due to the Using of Agent - winarsih, Winarsih (JOURNAL OF PRIVATE AND COMMERCIAL LAW, 2017)
Branchless banking is a new system which is implemented by banks in Indonesiawith aims to provide services to rural communities in order to access bankingservices such as lending or deposit money in the bank through an intermediaryagent. At first the rural communities are hard to obtain banking facilities such asmicro-credit whereas economic activities are largely actuated by lower-classsector therefore the Financial Services Authority or Otoritas Jasa Keuangan (OJK)issued the regulation number. 19/POJK.03/2014 about the financial serviceswithout office in the framework of financial inclusion on November 18, 2014 toface it. In this regulation, there are several things that need to be reviewed suchassessment accountability arrangements of agent as a third party who is notclearly regulated whereas according to some research there are some risk in themechanism of implementation like as potential of fraud due to the using of agentin this system. Though basically branchless banking is one of the strategicnational strategies to provide financing to small businesses in rural areas in orderto increase the competitiveness of products to compete in the ASEAN economiccommunity. Therefore, a legal instrument that can ensure and provide legalcertainty in branchless banking system is a very important thing, more overbranchless banking is the strategic of government to develop the quality of therural economy to face the ASEAN economic community.